Medical law in Japan - Kai, Katsunori, 1954- (Kluwer Law International B. V., 2022)
Derived from the renowned multi-volume 'International Encyclopaedia of Laws', this convenient volume provides comprehensive analysis of the law affecting the physician-patient relationship in Japan. Cutting across the traditional compartments with which lawyers are familiar, medical law is concerned with issues arising from this relationship, and not with the many wider juridical relations involved in the broader field of health care law.